Diving video-assisted analysis research - Long, M. Q. (Advances in Engineering Research, 2016)
According to the characteristics of the diving sports, a video analysis system is developed for diving sports in the paper. This system is mainly used in assisting coach to instruct athletes more effectively, and it can help the judgers give the correct judgments. Three components are composed in the research, the video analysis, 3D motion simulation and edit interface and the management of database. The background and meaning of developing this system is stated in the first section, and then the relation and the data flow are analyzed among the main modules. In the end, the key techniques and innovations are addressed in detail. In practice, this system can not only improve the efficiency of training, reduce the repeated training and the probability of false judgments, but also there is the high efficiency in the system and it is easy to be operated.